The robo-battle of Mega Tortoise vs. Hazard Hare : a graphic novel - Peters, Stephanie True, 1965- (Far out fables, 2018)
In this graphic version of the classic fable there is a new contest at the spring festival--a robot battle--and Shelly the Tortoise is determined to build a robot that can defeat that perennial winner and all around jerk, Hunter the Hare--especially after he steals her prototype suit.